Uji Eksperimen Inovasi Pembangkit Listrik Tenaga Surya Untuk Menggerakan Microbubble Kolam Ikan - Sofwan Hidayat; Jojo Sumarjo; Rizal Hanifi (Peneliti.net, 2023)
According to the solar insolation map, Indonesia has enough potential for solar electricity of 4.5 KW/m2/day. Solar energy can be utilized as hydroelectric power by receiving heat and converting it into electricity using solar cells (photovoltaic). The need for an electric load of 393 watts per hour to drive a 250w pump, a 23w DC motor, and a 3w lamp for 6 hours each. The photovoltaic solar cells used are polycrystalline 150 Wp and monocrystaline 150 Wp so the total solar panels used are 300 WP. The Solar Panel is installed with other components in the PLTS system such as a 20A controller, and a 12v 150Ah battery, while as a safety this battery uses the XH-M604 and XH-M609 modules as auto cut off when the current is over or below standard voltage. With calculations and several tests. The result is that using calculations based on formulas and panel theory with an efficiency of 15.1% can produce a power of 234.37 watts per hour while the panels are installed fixed at a tilt angle of 15° and an azimuth angle of 0°. The results of field testing with data on the average power generated per hour are 124.5 watts per hour, while the power required by the PLTS load is 144.2 watts per hour, and the results from the Disolved oxygen test are an average increase of 1.8 mg/L for 6 hours using the Microbuble Generator.